2018
DOI: 10.1002/ldr.3068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land‐use changes on runoff and sediment yield: Implications for soil conservation and forest management in Xishuangbanna, Southwest China

Abstract: Effects of vegetation traits and soil physical properties on runoff and sediment yieldwere investigated under different land uses in Xishuangbanna, Southwest China.The cutting-ring method was applied, and field plot experiments were conducted to determine soil physical properties and monitor runoff and sediment yield in response to land-use change by comparing tropical rainforest (TR), rubber monoculture (Rm), and four rubber-based agroforestry systems. Results showed that conversion of tropical forest to rubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…The increasing temperature also changes the distribution of runoff [4], and as has been observed during the past few decades, global temperature has increased significantly [5]. Similarly, land use changes directly affect the process of flow generation, which significantly changes runoff [6]. Researchers have concluded that half of the global surface and subsurface water has been used by humans, and due to a recent increase in agriculture and industrial activities this demand is increasing day by day [7].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing temperature also changes the distribution of runoff [4], and as has been observed during the past few decades, global temperature has increased significantly [5]. Similarly, land use changes directly affect the process of flow generation, which significantly changes runoff [6]. Researchers have concluded that half of the global surface and subsurface water has been used by humans, and due to a recent increase in agriculture and industrial activities this demand is increasing day by day [7].…”
Section: Introductionmentioning
confidence: 99%
“…The higher loss rate in the RPs could have been caused by agricultural activities, such as terracing and fertilization, which substantially decreased the plant litter input and stimulated microbial decomposition of the SOM in aggregates (Heinz et al, 2015). Moreover, soil C loss and redistribution in rubber monoculture are due to relatively high surface runoff and soil erosion rates under humid‐hot climatic conditions (Zhu et al, 2018). After 10 years of rubber cultivation, the C losses in the topsoil (0–10 cm) from forests in Bukit, Sumatra Island, Indonesia (Guillaume, Muhammad, & Kuzyakov, 2015) were much lower than those of RP 15 from TSR in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The trends suggest that the F I G U R E 7 Fourier transform infrared spectra for SPC in bulk soil under different land-use types. (Note: CK and S = 0 and 60 mg g −1 exogenous Pb in soils, respectively) [Colour figure can be viewed at wileyonlinelibrary.com] multilayered canopy in forests significantly increases the amount of stand litter and SOM, as well as fine particles, compared with RPs with a single-layered canopy (Zhu et al, 2018). This phenomenon improves the maximum soil absorption capacity for Pb and nutrient bioavailability by increasing the interfacial areas of the soil multiphase system of solid, liquid, and gas phases, as well as the quantity and stability of soil microaggregates (Jiang et al, 2017).…”
Section: Changes In the Soil Pool Capacity For Pb After Conversion mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results revealed that the ecosystem service function of haze absorption by green space in China from 2001 to 2018 shows a trend of first increasing and then decreasing, suggesting that the forest area with high haze absorbing capacity should be increased when adjusting the structure of ecological land use, and the occupation of cultivated land due to the rapid expansion of construction land should be regulated to improve the ability of green space to alleviate haze. Previous literatures explored the responses of ecosystem service functions to land use change, mainly through analyses of water yield (Li et al 2018), soil conservation (Zhu et al 2018), habitat quality (Dai et al 2019), biodiversity protection (Reiss and Chifflard 2018), and climate regulation (Yang and Wang 2019). However, there are few studies on the haze absorption by green space.…”
Section: Coefficient Of Sensitivitymentioning
confidence: 99%